Accelerating legalization and branding to enhance market access of Kampung Madu MSMEs, Kediri Regency - Lilik Purwanti; Iwan Triyuwono; Ghozali Maski; Melinda Ibrahim; Aryo Prakoso; Paras Imani; Romi Muharrom (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
Kampung Madu in Kediri Regency has been known as a center of beekeeping activities since the 1980s. However, most honey MSMEs still face limitations in business legality, halal certification readiness, and product branding, which hinder their access to wider markets and government empowerment programs. This community service program aimed to strengthen the business capacity of honey MSMEs through business legalization assistance and the development of a collective visual identity. The program was implemented from October 2025 to January 2026 through socialization, workshops, mentoring, participatory logo design, and evaluation activities involving 30 MSME partners. The results showed that 23 MSMEs successfully obtained a Business Identification Number (NIB), while 10 MSMEs completed the required documents for halal certification submission. In addition, a collective logo for Kampung Madu was successfully developed as a shared branding identity. Participants also demonstrated improved understanding of business legality and branding after participating in the program. These outcomes contributed to strengthening the legal and branding foundations of Kampung Madu MSMEs, thereby supporting broader market access and encouraging the sustainability of local honey-based businesses.